Impact of Overlapped AoAs on the Achievable Uplink Rate of Hybrid Beamforming for Massive MIMO mm-Wave Systems for Industrial Environments - Osama Alluhaibi (IEEE Access, 2019)
In this paper, we develop novel precoder and combiner schemes for multi-user hybrid digital-to-analog (D-A) beamforming for uplink massive multiple-input multiple-output millimeter wave (mm-Wave) systems, where the number of radio frequency chains is much smaller than the number of antennas each transceiver is equipped with. Industry 4.0 targets to accelerate the digitalization of manufacturing processes by allocating fixed and mobile robotics which use wireless communication. Such development requires high data throughput for which the utilization of short distance wireless communication such as mm-Wave system is crucially required. Based on our measurements, the probability of mm-Wave propagation waves to be reflected and refracted from metallic surfaces are shown to be significantly high. Consequently, uplink transmissions from different users such as robotics, machines, and sensors can go through paths sharing the same physical scatters, some transmission paths of different users may have overlapped angle of arrivals (AoAs) at the base station. Under such circumstance, the correlation between the channel vectors also increases considerably, which affects the achievable uplink rate severely. Therefore, the intrinsic focus is on substantially maximizing the desired signal while reducing the system interference. The proposed analog precoders and combiners are designed by using the power iteration and the Riemannian optimization method based on Stiefel manifold algorithms, respectively. The proposed digital combiner adapts the minimum mean-square error by judiciously exploiting the effective uplink analog channel gains. Furthermore, the channel estimation is investigated through a newly designed two-step procedure. In each scattering point, there is the strongest power point which is detected and then used to improve the accuracy by employing an angular domain scheme. The impact of this paper will be the boosting of the achievable uplink rate in industrial environments.